Is the platelet-to-lymphocyte ratio a new prognostic marker in multiple myeloma? - Solmaz, Şerife; Uzun, Özcan; Acar, Celal; Sevindik, Ömür Gökmen; Pişkin, Özden; Özsan, Hayri Güner; Demirkan, Fatih; Ündar, Bülent; Alacacıoğlu, Ahmet; Özcan, Mehmet Ali; Alacacıoğlu, İnci (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Recent reports showed neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR), as a predictor of progression-free survival (PFS) and overall survival (OS) in various malignancies. MATERIALS AND METHODS: We retrospectively examined the PLR, NLR, and MLR in a cohort of 186 newly diagnosed multiple myeloma (MM) patients. This study investigated the prognostic relevance of NLR, PLR, and MLR in MM patients. NLR, PLR, and MLR were calculated from whole blood counts before therapy. The Kaplan-Meier curves and multivariate Cox models were used for the evaluation of survival. RESULTS: Applying cutoff of 1.9 (NLR), 120.00 (PLR), and 0.27 (MLR), decreased PLR showed a negative impact on the outcome. Decreased PLR is an independent predictor for PFS and OS. There were no significant differences in median survival between the high and low NLR (P = 0.80) and MLR (P= 0.87) groups. CONCLUSIONS: In this study, thrombocytopenia and low PLR are associated with poor survival in MM patients does this P value apply to thrombocytopenia or low PLR and may serve as the cost-effective prognostic biomarker.
WOS: 000458270100001
PubMed ID: 30498304
Keywords: Multiple Myeloma; Neutrophil-to-lymphocyte Ratio; New Prognostic Marker; Platelet-to-lymphocyte Ratio